Long-Term Follow-Up of the Impacts on Obstetric Complications of Trunk Burn Injuries Sustained During Childhood - Duke, Janine; Wood, Fiona; Semmens, James; Edgar, D.; Rea, S. (Lippincott Williams & Wilkins, Inc., 2012)
Limited data are available to assess the long-term effects of burns to the trunk sustained during early childhood on subsequent pregnancies. This population-based retrospective longitudinal study uses linked Western Australia hospital morbidity and midwives notification data for the period 1983–2008. During the study period, 824 girls younger than 15 years with non-erythema burns (partial thickness, full thickness, or unspecified burn depth) to the trunk were hospitalized in Western Australia. During the follow-up, 134 subjects with burns to the trunk during childhood were identified as having later pregnancies. The mean age at admission for burn injury was 5.7 ± 4.0 years, and the majority of burns were caused by scalds (51.5%) and flame (37.3%). For these subjects (N = 134), there were a total of 213 subsequent pregnancies. All pregnancies resulted in full-term live births. There were 142 (64.3%) vaginal deliveries, 26 (12.2%) breech or instrument, and 45 (21.2%) deliveries were by cesarean section. No admissions for scar conditions or revisions of burn scar or contracture were identified during any pregnancy (first to fourth) for subjects with burns to the trunk. Mode of delivery was not statistically significantly different from that experienced by subjects with burns sustained during childhood to other anatomical sites. For subjects in this study with less severe burns to the trunk, no specific detrimental impacts during pregnancy or delivery or to the fetus were identified. Further surveillance is required to gauge an accurate assessment of complications associated with severe trunk burns sustained during childhood.